Pertanian Organik sebagai Salah Satu Konsep Pertanian Berkelanjutan - Yuriansyah Yuriansyah; Dulbari Dulbari; Hery Sutrisno; Arief Maksum (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Excessive use of inorganic chemicals results in adverse impacts on land and plants. In the midst of the community, there is anxiety about the high content of pesticide residues in agricultural products. There is a need to develop alternative farming systems that are able to produce quantities and quality of healthy products in a sustainable manner. One agricultural system that supports the concept is the organic farming system. The basic principles of organic farming are: (1) Keeping the ecosystem healthy, (2) Applying the principle of efficiency to the cultivation system, (3) Conducting production activities with the concept of sustainable agriculture, (4) Producing pesticide-free products, and (6) Maintaining environmental sustainability. Food Crop Production Study Program Lampung State Polytechnic makes Organic Agriculture as one of the leading competencies for its graduates. The establishment of the Organic Agriculture Business Unit on campus will increase student competencies, foster entrepreneurship, be a place for competency internships, and as an independent source of income.